2020
DOI: 10.1016/j.heliyon.2020.e04880
|View full text |Cite
|
Sign up to set email alerts
|

Reviewer's communication style in YouTube product-review videos: does it affect channel loyalty?

Abstract: Product-review videos can be a promising marketing method. The popularity of using videos as a medium for product reviews is evidenced by the number of channels that are used to provide product reviews on multiple platforms. Reviewers can use various strategies to attract wider audiences and make these audiences loyal to their channels. This study analyzes the effect of the reviewer's communication style on the audience's loyalty to the channels that provide product reviews, especially on the YouTube platform.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 42 publications
1
8
0
Order By: Relevance
“…According to Hsu and Liao (2014, p. 836) "a website is considered sticky when its users spend an above-average amount of time browsing it, when they visit the site frequently." The main means of generating stickiness on a website or social platform are the content (Hu et al, 2020;Lu & Lee, 2010;Xu et al, 2018) and communication style (Fitriani et al, 2020). Lu and Lee (2010) indicate that if you know your audiences, companies from all sectors can create specific contents which give them the opportunity to increase stickiness.…”
Section: Conceptual Framework and Hypothesismentioning
confidence: 99%
See 1 more Smart Citation
“…According to Hsu and Liao (2014, p. 836) "a website is considered sticky when its users spend an above-average amount of time browsing it, when they visit the site frequently." The main means of generating stickiness on a website or social platform are the content (Hu et al, 2020;Lu & Lee, 2010;Xu et al, 2018) and communication style (Fitriani et al, 2020). Lu and Lee (2010) indicate that if you know your audiences, companies from all sectors can create specific contents which give them the opportunity to increase stickiness.…”
Section: Conceptual Framework and Hypothesismentioning
confidence: 99%
“…Motivation seems to have a more relevant role than emotions, insomuch as motivations can explain a user's satisfaction with social network services regardless of whether the users feel positive or negative emotions (Pappas et al, 2020). From another perspective, Camilleri and Falzon (2020) indicate the importance of ritualized motivations in the use of streaming technologies, and Fitriani et al (2020) show that the utilitarian motivation (credibility) influences channel engagement. As a consequence, it can be said that motivation is an extension of demand, which will lead to the emergence of behaviour (Bi & Tang, 2017).…”
Section: Conceptual Framework and Hypothesismentioning
confidence: 99%
“…The pleasure obtained when using a new technology affects the intention to utilize digital media [40,64]. This is because some previous studies confirmed that hedonic motivation (HM) predicted behavioral intention (BI) towards using online learning media [40,65,66]. It is also observed to have influential abilities on teachers and students regarding the utilization of mobile learning technology [62,67].…”
Section: Hedonic Motivation (Hm)mentioning
confidence: 95%
“…The pleasure obtained when using a new technology affects the intention to utilize digital media [40,64]. This is because some previous studies confirmed that hedonic motivation (HM) predicted behavioral intention (BI) towards using online learning media [40,65,66].…”
Section: Hedonic Motivation (Hm)mentioning
confidence: 98%
See 1 more Smart Citation